Destructive and non-destructive measurements of NORM in monazite-rich sands of Brazil. (November 2017) - Larijani, C.; Schwendner, P.; Cockell, C.; Ivanov, P.; Russell, B.; Aitken-Smith, P.; Pearce, A.K.; Regan, P.H.
Abstract: The specific activity concentration of eight sand samples from three locations in the State of Espirito Santo, South Eastern Brazil have been determined for members of the 238 U and 232 Th decay series, as well as the primordial radionuclide 40 K. The calculated activity concentration values and associated radiation hazard indices were evaluated. The thorium decay chain activities are significantly higher than that of comparable studies from other areas of the world, leading to calculated absorbed dose rate in air and radium equivalent activities which are higher than world averages. This is attributed to the geology of the monazite material which is ubiquitous in this region of Brazil. Trace elemental analysis was also carried out on these samples using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Highlights: Measurement of Naturally Occurring Radioactive Materials. Specific activity concentration of 8 sand samples from three locations in the State of Espirito Santo, South Eastern Brazil have been determined. Trace elemental analysis and activity concentration measurement were carried out on the samples using Inductively Coupled Plasma Mass Spectrometry (ICP-MS).